Overview Of Patient Treatment Compliance Type 2 Diabetes Mellitus At Seyegan Health Center Sleman District In 2023 - Sebastian, Giovanno; Muttaqin, Ridwan (Indonesian Scientific Publication, 2024)
Diabetes mellitus is a chronic metabolic disorder characterized by increased blood sugar levels caused by impaired insulin secretion and function or both. If left untreated, diabetes mellitus can cause various macro and microvascular complications and has high morbidity and mortality. DaIn Seyegan Health Center patient visits from January to October 2023 there were 11,583 visits for type 2 diabetes mellitus, of which 1,281 visits were for type 2 diabetes mellitus with complications. Research objectives: This study aims to assess the description of medication adherence in type 2 diabetes mellitus patients at the Seyegan Community Health Center. The design of this research is descriptive to see the picture of compliance with the use of oral anti- diabetic drugs in patients with type 2 diabetes mellitus at the Seyegan Community Health Center, Sleman Regency for the period November 2023. The sample for this study is outpatients at general polyclinics who suffer from type 2 diabetes mellitus who included in the inclusion criteria. The measuring instrument used in this research is the MMAS-8 questionnaire. Based on an assessment using the MMAS-8 questionnaire, it was concluded that 26 (43.3%) respondents were considered to have low compliance in taking anti-diabetic drugs. Meanwhile, 14 (23.3%) respondents were considered to have moderate compliance and 20 (33.3%) respondents had high compliance in taking anti-diabetic drugs. Of the 60 respondents involved in the sample, 26 (43.3%) respondents were considered to still have low compliance in taking anti-diabetic drugs. Future researchers are advised to carry out an analysis of various factors that influence a person's taking medication and other factors such as family support and comorbid diseases.